Anti-Mycobacterial and Toxicity Activities of Some Priority Medicinal Plants from Lake Victoria Basin, Tanzania - Magadula, Joseph J.; Otieno, Joseph N.; Nondo, Ramadhani S.; Kirimuhuzya, Claude; Kadukuli, E.; Orodho, John A.; Okemo, Paul (European Journal of Medicinal Plants, 2012)
This study has evaluated ethanol extracts from five medicinal plants selected through ethnobotanical study from Lake Victoria basin, Tanzania for their in vitro antimycobacterial activity against two Mycobacterium species and cytotoxicity against brine shrimp larvae. Study Design: Laboratory experimental tests. Place and Duration of Study: Institute of Traditional Medicine, Muhimbili University of Health and Allied Sciences, P.O. Box 65001, Dar es Salaam, Tanzania, between July 2010 and July 2011. Methodology: Five medicinal plants were selected from the priority list obtained from Lake Victoria basin, Tanzanian side. Collection, processing and drying of plant samples were done in the field with the assistance of a botanist while extraction and concentration of plant samples to obtain crude extracts were done in the laboratory following standard procedures. The plants included in this study are Antidesma membranaceum, Crassocephalum manii, Entada abyssinica, Croton dichogamus and Rubia cordifolia. The two fold microdilution method was used to determine the MIC values of extracts against Research Article European Journal of Medicinal Plants, 2(2): 125-131, 2012 126 two Mycobacterium marker strains (Mycobacterium indicus pranii and Mycobacterium madagascariense). The cytotoxicity of plant extract was evaluated against brine shrimp larvae. Furthermore, the extracts were screened phytochemicaly to establish the group of compounds responsible for the activity.
Keywords: Extracts; Phytochemical screening; Anti-mycobacterial; Cytotoxicity; Lake Victoria basin.; Tanzania